The completeness, accuracy and impact on alerts, of wearable vital signs monitoring in hospitalised patients - Anthony J. Wilson; Alexander J. Parker; Gareth B. Kitchen; Andrew Martin; Lukas Hughes-Noehrer; Mahesh Nirmalan; Niels Peek; Glen P. Martin; Fiona C. Thistlethwaite (BMC Digital Health)
Abstract Background Use of wearable vital signs sensors (WVSSs) to monitor hospitalised patients is growing but uncertainty exists about how such sensors should be adopted into existing practice. The aim of this observational study was to determine the completeness of data capture and accuracy of measurements recorded by a suite of WVSSs. The implications of using such measurements to derive early warning scores was also assessed. Methods Adult inpatients with Covid-19 wore four WVSSs recording heart rate/respiratory rate (HR/RR), oxygen saturation (SpO2), axillary temperature and blood pressure (BP). Wearable vitals were paired with traditional vitals (measured by nurses) recorded concurrently. The accuracy of the wearable vitals was assessed using traditional vitals as the reference. National early warning (NEWS2) scores were calculated using wearable and traditional vitals. Results Forty-eight patients were monitored for 204 days with the sensors. Median sensor wear was 3.9(IQR:1.7–5.9), 3.9(IQR:1.6–5.9) and 3.8(IQR:0.9–5.9) days for HR/RR, temperature and SpO2 respectively. The BP cuff was worn for median 1.9(IQR:0.9–3.8) days in 33 patients. Length of hospital stay was 8(IQR:6–13) days. Completeness of data capture was 84% for HR/RR, 98% for temperature, 72% for SpO2 and 36% for BP. There were 1633 HR, 1614 RR, 1412 temperature, 1294 SpO2 and 59 BP wearable-traditional measurement pairs. 59.7% of HR pairs were within ± 5 bpm, 38.5% of RR pairs within ± 3breaths/min, 24.4% of temperature pairs within ± 0.3℃, 32.9% of SpO2 pairs within ± 2% and 39.0% of BP pairs within ± 10 mmHg. Agreement between wearable and traditional RRs was poor at high RRs. In a ward setting, 613 NEWS2 scores were calculated using wearable-traditional HR, RR, temperature and SpO2 pairs. The median NEWS2traditional was 1(IQR:1–2) and the median NEWS2wearable was 4(IQR:3–6). Using traditional NEWS2 alerts as a reference, 86% (225/262) of wearable NEWS2 5 + alerts and 89% (82/92) of wearable NEWS2 7 + alerts were false positives. Conclusions Agreement between vital signs recorded by wearable sensors and concurrent traditional vitals is poor. In this context, data from wearable sensors should not be used in existing track and trigger systems. Trial registration The COSMIC-19 study was registered with clinicaltrials.gov (registration: NCT04581031, date of registration: Oct 6th 2020).